Implementation of Preemptive Goal Programming and Branch and Bound in Production Planning at the Istiqomah Tofu Factory, Bandar Lampung City - Anggraini, Retno; Irwan, Sri Efrinita; Nasution, Achmad Suryadi (Syiah Kuala University, 2023)
In a production process, it is necessary to carry out a production planning so that the company gets the maximum profit at the minimum cost. Each place of production has several goals to be achieved, these goals do not always have the same level of importance. There are several goals that have varying degrees of importance. This problem can be solved by using the preemptive goal and branch and bond method. The results of the study show that, to achieve all the desired goals/objectives the Istiqomah tofu factory has to produce 638 packs of white tofu, 360 packs of yellow tofu and 360 packs of Chinese tofu so that the factory's profit could increase by 13.43% or Rp237.000,00perday.